Blood Flow After Exercise-Induced Muscle Damage - Selkow, Noelle M. (J Athl Train, 2015)
CONTEXT: The most common modality used to address acute inflammation is cryotherapy. Whereas pain decreases with cryotherapy, evidence that changes occur in perfusion of skeletal muscle is limited. We do not know whether ice attenuates the increases in perfusion associated with acute inflammation. OBJECTIVE: To examine the effects of repeated applications of ice bags on perfusion of the gastrocnemius muscle after an eccentric exercise protocol. DESIGN: Controlled laboratory study. SETTING: Laboratory. PATIENTS OR OTHER PARTICIPANTS: Eighteen healthy participants (3 men, 15 women; age = 22.2 ± 2.2 years, height = 166.0 ± 11.9 cm, mass = 69.4 ± 25.0 kg). INTERVENTION(S): To induce eccentric muscle damage, participants performed 100 unilateral heel-lowering exercises off a step to the beat of a metronome. A randomized intervention (cryotherapy, sham, control) was applied to the exercised lower extremity immediately after the protocol and again at 10, 24, and 34 hours after the protocol. MAIN OUTCOME MEASURE(S): Baseline perfusion measurements (blood volume, blood flow, and blood flow velocity) were taken using contrast-enhanced ultrasound of the exercised leg. Perfusion was reassessed after the first intervention and 48 hours after the protocol as percentage change scores. Pain was measured with a visual analog scale at baseline and at 10, 24, 34, and 48 hours after the protocol. Separate repeated-measures analyses of variance were used to assess each dependent variable. RESULTS: We found no interactions among interventions for microvascular perfusion. Blood volume and blood flow, however, increased in all conditions at 48 hours after exercise (P < .001), and blood flow velocity decreased postintervention from baseline (P = .041). We found a time-by-intervention interaction for pain (P = .009). Visual analog scale scores were lower for the cryotherapy group than for the control group at 34 and 48 hours after exercise. CONCLUSIONS: Whereas eccentric muscle damage resulted in increased blood flow, ice did not decrease muscle perfusion 48 hours after exercise. Therefore, ice does not seem to decrease muscle perfusion when blood flow is elevated, as it would be during inflammation.